Balancing Responsibility: What model works for Europe? - Karsten Neuhoff (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
We first discuss different rules for pricing and provision of balancing across EU member states and their implications. Some member states face significant transmission constraints inside their pricing zone(s). In principle, this can be avoided with smaller pricing zones and in some instances transmission expansion. We discuss in the second part, how in practice different strategies are pursued to accommodate internal transmission constraints within balancing mechanisms. European market integration has to date focused on enhancing day-ahead trading. We discuss in a third part the experience, benefits and perspectives for better integrating balancing mechanisms across EU member states before we conclude.
Keywords: 330